Proof of work algorithm based on credit model - Zuan WANG; Youliang TIAN; Qiuxian LI; Xinhuan YANG (Tongxin xuebao)
A consensus protocol based on the credit model was proposed.Firstly,the consensus agreement drew on the idea of personal credit risk assessment and a node credit model based on BP neural network was designed.Secondly,a piecewise rotation model was also constructed to segment the search space according to the node’s credit level to generate new blocks.At the same time,the possible attack of the protocol was analyzed and the vulnerability of this protocol was fixed.Finally,the simulation experiments show that the protocol not only effectively reduces the huge resource consumption in the process of new block generation,but also suppresses the generation of the large mine pool,making the whole blockchain system more secure and reliable.